Oral History Interview: Juliet Thorner, M.D. - Thorner, Juliet M.D.
Born Indianapolis, Indiana, in 1910, Thorner later became a pediatric doctor. Her perspective is very interesting since she had personal contact with many poor migrant families and their children. She came out to Kern General hospital in 1937 and ran the pediatric ward. Her account of the tragic state of affairs at the hospital includes understaffing and the migrants' lack of health education. Her graphic accounts of the health crisis that existed in the camps are shocking. She also describes some home remedies used by some of the migrants and a local perspective of the "Okies."